Prevalence of Extended-Spectrum Beta-Lactamase (ESBL) Producing Escherichia coli in the Intestinal Flora of Pet Cats - Marshanda Venda Dora Putri Aziz; Kuntaman Kuntaman; Masfufatun Masfufatun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Antimicrobial resistance (AMR) has become a serious global health issue, affecting both humans and pets. Cats, which frequently interact closely with humans, can serve as reservoirs of resistant Escherichia coli. This study aimed to assess the prevalence of ESBL-producing Escherichia coli in the intestinal flora of pet cats in Balongbendo, Sidoarjo, applying a One Health approach to explore the transmission interface between animals, humans, and the environment.A descriptive observational study with a cross-sectional design was conducted. A total of 50 fecal samples were collected by simple random sampling from pet cats in RW 01, Desa Jabaran, Sidoarjo (January–February 2025). Samples were incubated on MacConkey agar enriched with 4 µg/mL cefotaxime for screening ESBL, and confirmation was conducted utilizing the Double Disk Synergy Test (DDST). Prevalence was determined as the ratio of positive isolates to the overall total . The results showed that 20 of 50 samples (40%) were positive for ESBL-producing Escherichia coli. The highest prevalence was found in Area 1 (60%), which was characterized by poor sanitation and high population density. This indicates widespread ESBL-producing Escherichia coli in domestic animals and underscores the risk of cross-transmission to humans. Therefore, educating animal owners, monitoring antibiotics, and ensuring environmental sanitation are crucial for preventing cross-transmission to humans.